2004
DOI: 10.1089/adt.2004.2.525
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an Atomic Absorption Rubidium Ion Efflux Assay for KCNQ/M-Channels Using the Ion Channel Reader 8000

Abstract: M-channels (M-current), encoded by KCNQ2/3 K(+) channel genes, have emerged as novel drug targets for a number of neurological disorders. The lack of direct high throughput assays combined with the low throughput of conventional electrophysiology (EP) has impeded rapid screening and evaluation of K(+)-channel modulators. Development of a sensitive and efficient assay for the direct measurement of M-current activity is critical for identifying novel M-channel modulators and subsequent investigation of their the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Previous studies reported Z ’‐values of 0.73 and 0.81 for the Rb efflux assay using an automated F‐AAS procedure. [ 15,16 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies reported Z ’‐values of 0.73 and 0.81 for the Rb efflux assay using an automated F‐AAS procedure. [ 15,16 ]…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported Z'-values of 0.73 and 0.81 for the Rb efflux assay using an automated F-AAS procedure. [15,16] The Z'-factor was also determined for the present GF-AAS-based Rb efflux assay based on the data from 10 experiments (Figure 4a) performed during assay development and validation. Figure 4b shows the calculated Z'-factors.…”
Section: Quality and Performance Of The Rb Efflux Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…In literature one can find the description of all kinds of the ion channels implemented on the basis of the graphene nanopores/nanochannels [96,97]: for alkali metals [98], including biomimetic (bioinspired) analogs of the sodium and potassium channels [99] (as well as the other alkali metals, such as lithium, rubidium, and caesium [100][101][102], as follows from the thermodynamic calculations for the monovalent cations [103] and quantum chemical simulations for a number of the alkali metal ions [104], which can also operate in the channelome, but their clark is too low, and hence, does not allow to perform any significant functions at the macroscopic scale at the organism or the whole biosphere level), for the chloride ions [105] (the analogs of the known chloride ion channels [106,107]), etc. Consideration of the "exotic" pores and channels in graphene operating with the rubidium, gadolinium and other rare earth element ions [108,109] is beyond the scope of NANOSYSTEMS this paper for the purpose of maintenance of the biomimetic functional analogy.…”
Section: Pores and Ion Channels In Graphene-based Nanostructuresmentioning
confidence: 99%
“…6B), potentially because of the nature of the non-GOhm seal of IonWorks and its resultant voltage error. When the IonWorks EC 50 s were compared with those generated with Rb + efflux using previously established methodology, 28 only a low correlation (R 2 = 0.4) was found (Table 3). It was also clear with the Rb + efflux assay that a poor correlation occurred between the maximum effects observed in Rb + and IonWorks (data not shown).…”
Section: Subcloning Of Rkcnq2/3 Stable Transfected Cellsmentioning
confidence: 99%